Nuovo realismo e metodi di ricerca misti - Alessandra La Marca (LED Edizioni Universitarie, 2014)
New Realism and Mixed Research Methods «New Realism» has highlighted the limits of social constructivism and of so-called «weak thought» that risks producing nihilism. Some prejudices have recently been removed that prevented researchers and theorists from grasping the real core of educational facts in their concrete evidence. However, an opening to a metaphysical view would offer «new realism» further epistemological perspectives. In this sense, the contribution of critical realism might help to overcome the artificial antinomy between the active role of the knowing subject and the objective measurement of educational facts. With this «opening», scientific knowledge and current knowledge would no longer be seen as opposites because the latter would be considered as a deepening of the former, in a line of continuity. The experimental methods of research in the education field have recently made use of the philosophical reflections of realists to integrate the quantitative and qualitative approach to the study of education. New research designs, aimed at monitoring and observing educational processes, without «encaging» them, are mainly of a «mixed» kind.